BEBERAPA UNSUR PEMBENTUK ESTETIKA KARAWITAN JAWA GAYA SURAKARTA - Joko Purwanto (Institut Seni Indonesia Surakarta, 2012)
This article was written based on a bibliographical study which used a number of references found in the library of Karawitan department at ISI Surakarta. An audio study was also carried out, using various references of Javanese karawitan from both commercial recordings and the writer’s own private collection. Other references were also downloaded from the internet, in particular those related to the topic of the study, namely the subject of aesthetics. From the results of the study it was discovered that there are at least two categories of elements which shape the aesthetics of karawitan, namely the primary elements and the special elements. The primary elements consist of 1) the infrastructure, 2) the tuning and melody, and 3) the artists. All three are equally important in creating the aesthetics of karawitan and all three are connected with one another. The other elements, which are no less important, are categorized as special elements. These include: irama, laya, cengkok, patterns, pathet, treatment, dynamics, time intervals, vocal elements, and culture. All of these elements are extremely important in relation to a karawitan performance. These special elements are also connected to each other. It is through these primary elements and special elements that a karawitan performance can be realized and the aesthetics of karawitan can take shape. Key words : infrastructure, tuning and melody, artist Pengantar